Perencanaan Produksi dan Manajemen Persediaan pada Perusahaan Kue dan Roti - Fazlur Rahman Lutfi; Catur Sasongko (Studi Akuntansi dan Keuangan Indonesia, 2022)
This research was conducted with the aim of evaluating the process of production planning and inventory management applied by the cake and bakery company PT ABC, as well as recommending an appropriate and comprehensive method so that it can overcome production and inventory problems that have been faced by the company. The research was conducted by observing the manufacturing company PT ABC, a cake and bakery company in South Jakarta. The data used are primary and secondary data, in the form of interviews conducted on the management and employees of PT ABC, as well as the company's historical data. The results of the research are in the form of evaluation of production planning in the process of demand forecasting and preparation of master production schedules. In addition, researchers also evaluate inventory management related to the production process by proposing the Material Requirement Planning (MRP) method, calculating inventory turnover ratios, and horizontal analysis based on company report data from the previous period.